1991
DOI: 10.1051/apido:19910302
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a colony's queen state on the drifting of drone honey bees (Apis mellifera L)

Abstract: Summary — Drones were marked individually with numbered tags and introduced into pairs of hives that were spaced 1 m apart facing south. The queen state of one colony in each pair was altered (ie with a caged-virgin queen, caged-mated queen, mated-laying queen, queenless or pheromone trans-9-oxodecenoic acid) and the other member of the pair remained queenright. Drifting of 4 independent age groups of drones (5-10, 10-15, 15-20 and 20-25-d old) was studied. A higher proportion of drones drifted to colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For example, the coloration of the hive has been shown to reduce drifting [12,13,19,44]. For the drifting of drones the queenstate of the colony [7,8] must be considered too. The arrangement of colonies is among the most important factors [19][20][21]32]; e.g.…”
Section: Original Articlementioning
confidence: 99%
“…For example, the coloration of the hive has been shown to reduce drifting [12,13,19,44]. For the drifting of drones the queenstate of the colony [7,8] must be considered too. The arrangement of colonies is among the most important factors [19][20][21]32]; e.g.…”
Section: Original Articlementioning
confidence: 99%
“…High rates of drone drift have been reported in managed honey bee colonies, but this is likely an artefact of the high colony densities of these environments. Such drifting behavior is best documented in A. mellifera, where drones regularly return from drone flights to non-natal colonies within apiaries [25,26,45]. In these cases, drone drift is not random, but has a directional bias that corresponds to nest position (e.g., drones had a tendency to drift in a southward direction [26]) and decreases with greater distances between hives [23].…”
Section: Discussionmentioning
confidence: 99%
“…That is, drones could expand their effective flight range and mate at greater distances from their natal nest if they sometimes return to non-natal nests upon unsuccessful mating flights. This behavior is known as "drifting" [23][24][25][26]. Such drone drift occurs regularly in Apis mellifera hives kept in managed environments [24,26], where workers may allow males to enter the nest irrespective of whether it is the drones' nest of origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this characteristic, the sun and/or high light intensity are likely to be a reliable orientation cue, directing bees to their mating places. The use of cues based on the sun is known in many animals, and it has previously been suggested that the movement and position of the sun influence the orientation behavior of honeybee males (R. Currie, 1987; R. W. Currie & Jay, 1991). Indeed, the mating success and flight activity of males in this species remarkably decrease on cloudy and rainy days when these cues are unavailable and obscured (El‐Niweiri & Moritz, 2011; Lensky et al, 1985; Reyes et al, 2019; Waiker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%